1986
DOI: 10.1111/j.1532-5415.1986.tb06335.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage at Diagnosis of Cancer Varies With the Age of the Patient

Abstract: The stage of a cancer at diagnosis is multiply determined, theoretically depending on such disparate factors as tumor biology, patient education, and physician behaviors. Data from all Hispanic and non-Hispanic white residents of New Mexico diagnosed with a malignancy from 1969 through 1982 were analyzed to determine the relationship between the age of the patient and the stage of cancer at the time of diagnosis. Three general patterns were apparent. For cancers of the bladder, breast, cervix, ovary, thyroid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(48 citation statements)
references
References 18 publications
4
44
0
Order By: Relevance
“…We observed that patients' characteristics associated with delay comprise older age, history of benign mastopathy, obesity, not Older women are more prone to procrastinate early detection of breast cancer resulting in more advanced disease and fewer asymptomatic cases (Holmes and Hearne, 1981;Goodwin et al, 1986;Lickley, 1997). Similar findings have been reported from various countries (Polednak, 1986;Yancik et al, 1989;Coates et al, 1992;Afzelius et al, 1994;Fowble et al, 1994;Ramirez et al, 1999).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We observed that patients' characteristics associated with delay comprise older age, history of benign mastopathy, obesity, not Older women are more prone to procrastinate early detection of breast cancer resulting in more advanced disease and fewer asymptomatic cases (Holmes and Hearne, 1981;Goodwin et al, 1986;Lickley, 1997). Similar findings have been reported from various countries (Polednak, 1986;Yancik et al, 1989;Coates et al, 1992;Afzelius et al, 1994;Fowble et al, 1994;Ramirez et al, 1999).…”
Section: Discussionmentioning
confidence: 89%
“…Fatalism, e.g. a sense that one has lived long enough, might be another reason for the higher proportion of patient delay among older breast cancer patients (Facione, 1993;Goodwin et al, 1986;Lierman, 1988). …”
Section: Discussionmentioning
confidence: 99%
“…28 In another analysis, the percentage of patients with local stage disease was higher among those aged 75 to 84 years compared with those aged 55 years (39% vs 26%). 29 This was associated with a decline in the rate of advanced disease in the older patients (41% vs 46%).…”
Section: Discussionmentioning
confidence: 99%
“…Differences Finally, both delay and extent of disease at diagnosis may be related to age (Goodwin et al, 1986) (Hisserich et al, 1975;Mack, 1977). The method of case identification has been described elsewhere (Mack, 1977 (Breslow & Day, 1980).…”
mentioning
confidence: 99%